AN ANALYSIS OF THE ILLOCUTIONARY AND PERLOCUTIONARY ACTS IN “ONWARD” MOVIE - Wulan Wangi; Dewi Tri Wulandari; Yuli Sugianto (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
Communication is the most important part of human life. It does not only occur on social media, but also in drama or movies. However, communication which is only known by the speaker, will lead misunderstanding between the speaker and listener. Pragmatics is an appropriate analysis for interpreting a language. One of the important aspect in pragmatics is speech act. There are three levels of speech acts that can be found in utterances, namely locutionary, illlocutionary, and perlocutionary act. This research is a descriptive study of the illocutionary and perlocutionary acts in Onward movie. The researcher used descriptive-qualitative design and the documentation method to collect data. The researcher used several steps to collect data. The first step, the researcher searched and downloaded Onward movie and its script through the internet. Second, the researcher watched the movie and paid attention to the character’s utterances while reading the script simultaneously. Third, the researcher collected data from dialogues relevant to the research problems, namely the illocutionary and the perlocutionary act. Finally, the researcher grouped the speaker’s utterances with each type of illocutionary act and analyzed the perlocutionary act based on Austin’s theory. The results show that in Onward movie there are 31 types of illocutionary acts with 4 main types and 27 supporting types from the speaker, and 31 perlocutionary acts, namely 24 perlocutionary objects and 7 perlocutionary sequels made by the main character as the listener.